Estimation of Age by Modified Gustafson’s Method from Incisor and Canine Teeth - Ajay V Patil1, Chandrakant M Kokatanur2, Vinay S Bannur3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Estimating age from teeth is generally reliable as they are naturally preserved long after all the tissues and even bones have disintegrated. Aim of the study: The present study was an attempt to estimate the age of an individual by using modified Gustafson’s method from age related alteration in incisors and canines in Karad. Materials and methods: A cross sectional study was conducted in Karad for a period of 4 months from Nov 2018 to Feb 2019. Results: 95 teeth were observed, out of which 59 were incisors and 36 canines. The coefficient of variations among parameters ranged from 22.61 to 29.92%. Conclusion: - The estimated age error was minimized to 1.15 years. The age calculated by this method was found to be more accurate, reliable and reproducible